Measuring psychosocial determinants of vaccination behavior in healthcare professionals: validation of the Pro-VC-Be short-form questionnaire. (3rd October 2022) - Garrison, Amanda; Fressard, Lisa; Karlsson, Linda; Soveri, Anna; Fasce, Angelo; Lewandowsky, Stephan; Schmid, Philipp; Gagneur, Arnaud; Dubé, Eve; Verger, Pierre
ABSTRACT: Background: Vaccine confidence among health care professionals (HCPs) is a key determinant of vaccination behaviors. We validate a short-form version of the 31-item Pro-VC-Be (Health Professionals Vaccine Confidence and Behaviors) questionnaire that measures HCPs' confidence in and commitment to vaccination. Research design and methods: A cross-sectional survey among 2, 696 HCPs established a long-form tool to measure 10 dimensions of psychosocial determinants of vaccination behaviors. Confirmatory factor analysis (CFA) models tested the construct validity of 69, 984 combinations of items in a 10-item short form tool. The criterion validity of this tool was tested with four behavioral and attitudinal outcomes using weighted modified Poisson regressions. An immunization resource score was constructed from summing the responses of the dimensions that can influence HCPs' pro-vaccination behaviors: vaccine confidence, proactive efficacy, and trust in authorities. Results: The short-form tool showed good construct validity in CFA analyses (RMSEA = 0.035 [0.024; 0.045]; CFI = 0.956; TLI = 0.918; SRMR 0.027) and comparable criterion validity to the long-form tool. The immunization resource score showed excellent criterion validity. Conclusions: The Pro-VC-Be short-form showed good construct validity and criterion validity similar to the long-form and can therefore be used to measure determinants of vaccination behaviors among HCPs.